Methodical system for formation of professional competences of a future foreign language teacher in conditions of distance learning - Shakiyeva, Aida; Zhorabekova, Ainur; Abilkhairova, Zhanar; Yessimgaliyeva, Tlekshi; Makulbek, Azamat (Frontiers in Education, 2023)
This study's significance lies in its recognition of the evolving educational landscape and the need for a new type of specialist who can adapt to modern innovations and effectively implement digital tools and platforms in distance learning. In the context of the ongoing education reform in Kazakhstan, the study focuses on improving the quality of higher professional education to meet international standards. Specifically, it emphasizes the importance of training future teachers who are prepared to teach foreign languages through distance learning using digital resources. The main aim of the study is to describe a structured approach to teacher training by proposing a methodical system for the formation of professional competences of a future foreign language teacher in the conditions of distance learning at a university. The components of this system, such as aim, content, methods, forms, tools, and outcome, provide a comprehensive framework for developing the following competences: digital, psychologicalpedagogical, linguistic, foreign language communicative, and methodical competences. Additionally, the study introduces an elective course, "Organization and methods of distance learning of a foreign language," which serves as a practical implementation of the proposed methodical system. This course, when integrated into the curriculum of a pedagogical university, aims to equip future teachers with the necessary knowledge and skills to successfully navigate the challenges and opportunities presented by distance learning.